Gadget Use Habit by Primary School Students in the Post Pandemic Covid-19 - Oktavia Marageta; Yusnadi; Muhammad Takwin Machmud (International Journal of Educational Practice and Policy, 2023)
The purpose of this study is to examine elementary school students use of electronics following the Covid-19 epidemic. The descriptive quantitative research approach was applied. Questionnaires were provided to primary school children to collect data. The study was conducted in Tanjung Mulia Village, using 20 elementary school students as participants, and a sample technique called Simple Random sample was used. The data collecting approach used in this study is a closed questionnaire. The instrument is used by respondents through picking alternative answers that match their view or decision. In this study, descriptive data analysis is used to interpret the data gathered from questionnaires. According to the findings of the survey, the majority of elementary school students choose to use devices for amusement purposes such as playing games, viewing or listening to music, and excessively accessing social media without time limitations, rather than for study and school purposes. The use of gadgets as a source of learning and pleasure must be done with adequate supervision, such as restricting gadget usage time, managing gadget use exclusively on beneficial, educational apps, and accompanying and leading children.